KESIAPAN ALAT FORKLIFT DAN KETERAMPILAN OPERATOR TERHADAP KUALITAS KECEPATAN BONGKAR MUAT - Arsad Farezan; Zaldi zain; Muhammad Gufron (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research is entitled "Readiness of Forklift Equipment and Operator Skills on the Quality of Loading and Unloading Speed". This study aims to determine the effect of forklift readiness and operator skills on loading and unloading speed. The method used in this study is a quantitative method and the analytical technique used is multiple linear regression. The results of the study state that the readiness of the forklift equipment and the skills of the operator simultaneously (simultaneously) have a significant effect on loading and unloading speed. Partially, operator skills have a significant effect on the speed of loading and unloading, and the readiness of forklift tools also has a significant effect on the speed of loading and unloading.